Investigating the Effectiveness of Drug Administration and Relaxation Therapy in Reducing Pain and Sleep Disorders in Rheumatoid Arthritis Patients - Ghassemzadeh, Sogand; Rabiee, Sana; Sharifian jazi, Ashraf; Hashemi, Faezeh; Hosseini, Zeynab AI Sadat (Iranian Journal of Neurodevelopmental Disorders, 2024)
Objective: Rheumatoid arthritis is a long-lasting inflammatory condition that causes joint pain, stiffness, and sleep disorders, significantly impacting the well-being of individuals. The purpose of this research was to examine the efficacy of drug administration and relaxation therapy in alleviating pain and improving sleep quality in patients with rheumatoid arthritis. Methods and Materials: The study used a quasi-experimental research design, including pre-test, post-test, and four months’ follow-up. The study consisted of three groups: two experimental groups (one receiving drug therapy and the other receiving relaxation therapy) and a control group. The research included all patients diagnosed with rheumatoid arthritis and referred to the Iranian Rheumatology Center in Tehran from July to December 2023 as the statistical population. The sample included 60 participants who were selected using purposive sampling methods. In the drug therapy group, each patient was prescribed 3 mg of melatonin daily for one month. The relaxation therapy group, consisting of 20 participants, received six 90-minute sessions once a week, both in person and at home. The in-person sessions were held in suitable offices under the supervision of the Rheumatology Center. The research utilized the Pittsburgh Sleep Quality Index (PSQI) and the McGill Pain Questionnaire (MPQ) as research instruments. The data was analyzed statistically using the Kruskal-Wallis H method and analysis of covariance with repeated measures at a p-value of 0.05, utilizing SPSS statistical software version 27. Findings: Based on the findings, the P-value for Between-Subjects Effects showed significance for the sleep disorder variable (p<0.001). Similarly, there was significance in the interaction effects between time and groups for the sleep disorder variable (p=0.004). In addition, the P-value for Between-Subjects Effects was also significant for the sensory pain variable (p<0.001). The study also discovered that the relationship between time and groups, along with the impacts within each group, were both statistically significant for the sensory pain variable (p>0.05). However, no differences were observed in any of the groups and stages for the emotional pain variable, indicating that the intervention methods did not affect emotional pain. Conclusion: The current study found that drug therapy is successful in decreasing sleep disorders and providing long-term relief from sensory pain. On the other hand, relaxation therapy is not as effective as medication in reducing pain and sleep disorders. These findings will assist medical professionals in making informed decisions when selecting treatments for patients with rheumatoid arthritis.